Flavonoid from stem bark of Aquilaria microcarpa - Alfinda Kristanti, .- (Egyptian Chemical Society, 2018)
7-hydroxy-5,3’,4’-trimethoyflavon (1), a flavonoid, was isolated from stem bark of Aquilaria microcarpa, a species belonging to Thymelaeaceae that has not been investigated. The chemical structure has been elucidated based on spectroscopy FTIR, NMR and HRESI-MS analysis